Konversi Termal Kayu Ketapang (Terminalia Catappa) Menjadi Bio-Oil Dengan Teknologi Pirolisis Menggunakan Katalis Ni/Nza - Arbhy Indera Ikhwansyah; Syaiful Bahri; Edy Saputra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Availability of petroleum as a fuel that can not be updated further reduced by increasing the use of oil for human needs. For that we need to do a conversion innovation of energy that donot depend on fossil resources and can be renewable and have an output similar to that produced from fossil resources. One such innovation is the conversion of biomass derived from terminalia catappa wood to bio-oil. Bio-oil can be produced by pyrolysis of terminalia catappa wood with catalyst Ni/NZA. Objective this research to produce bio-oil from terminalia catappa wood as an alternative fuel, studying the effect of the weight ratio of the catalyst Ni/NZA to the biomass, studying the effect of metal impregnation Nickel (Ni) on Natural Zeolite deAluminated (NZA) and characterization of physical properties and chemical properties of bio-oil. Process pyrolysis was carried out at 320 0C, silinap 500 ml, 50 grams of biomass with + 100-200 mesh sieve size, variations in the catalyst Ni/NZA to thebiomass of 2%; 4% and 6% by weight and Ni metal variation on Natural Zeolite deAluminated (NZA) of 0%; 1%; 1,5% and 2%. The results of this study produce bio-oil yields the largest on the use of the catalyst Ni/NZA 4% by weight of the metal content of 2% by 68,22%. Characterization of physical properties of bio-oil obtained in the form of density 0,806 g/ml, 7,591 cSt viscosity, acidity 74,078 mg NaOH/g sample, flash point 45,971 0C andcalorific value 43,708 MJ/kg. While the characterization of the chemical properties of bio-oil using Gas Chromatography-Mass Spectroscopy (GCMS) obtained some dominant chemicalcomponents such as acetic acid and an area of 60,84%, 2-propanone with an area of 12,64%, 1,2-ethanediol with area of 8,60%, propionic acid and an area of 5,60% and methyl acetate and an area of 3,76%.Keywords: bio-oil, catalyst Ni/NZA, pyrolysis, terminalia catappa wood